2002
DOI: 10.1002/ijc.10336
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐infiltrating endothelial cells and endothelial precursor cells in inflammatory breast cancer

Abstract: Inflammatory breast cancer (IBC) isInflammatory breast cancer (IBC) is clinically characterized by rapid tumor enlargement with skin erythema. The disease tends to invade locally and metastasize systemically and the histopathologic features are consistent with an extremely aggressive phenotype. 1 Despite recent advances in strategies for multimodal treatment of patients with IBC, this disease is still considered incurable and there is a great need for further improvement of treatment strategies to combat this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 21 publications
(25 reference statements)
3
39
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF)-mobilized stem cells restored tumor angiogenesis and growth in Id-mutant mice (11). Clinically, a higher population of EPC is associated with inflammatory breast tumors versus a noninflammatory phenotype (12). Additionally, EPC have been detected in the circulation and malignant tissues of patients with multiple myeloma (13).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF)-mobilized stem cells restored tumor angiogenesis and growth in Id-mutant mice (11). Clinically, a higher population of EPC is associated with inflammatory breast tumors versus a noninflammatory phenotype (12). Additionally, EPC have been detected in the circulation and malignant tissues of patients with multiple myeloma (13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using a semiquantitative reverse transcriptase polymerase chain reaction, Shirakawa et al (2002b) showed that angiogenic, but not lymphangiogenic factors are overexpressed in resected specimens of 19 IBC patients when compared with 23 non-IBC tumours. In the same study, a significantly higher population of tumour-infiltrating endothelial cells or endothelial precursor cells was immunohistochemically found in the tumourassociated stroma of IBC specimens than in non-IBC specimens.…”
mentioning
confidence: 99%
“…The expression of Tie2 was believed to be confined to vascular structures (Yancopoulos et al, 2000). However, recent studies have identified Tie2 expression in nonvascular tissues, as in the hematopoietic system and in the nonvascular compartment of several types of cancer (Kukk et al, 1997;Shirakawa et al, 2002;Wang et al, 2005). Recently, our group reported Tie2 expression in neoplastic astrocytic cells in malignant human gliomas (Lee et al, 2006b).…”
mentioning
confidence: 99%